Neighbourhood-scale dispersion of traffic-induced ultrafine particles in central London: WRF large eddy simulations. (November 2020) - Zhong, Jian; Nikolova, Irina; Cai, Xiaoming; MacKenzie, A. Rob; Alam, Mohammed S.; Xu, Ruixin; Singh, Ajit; Harrison, Roy M.
Abstract: Traffic-generated ultrafine particles (UFPs) in the urban atmosphere have a high proportion of their composition comprised of semi-volatile compounds (SVOCs). The evaporation/condensation processes of these SVOCs can alter UFP number size distributions and play an important role in determining the fate of UFPs in urban areas. The neighbourhood-scale dispersion (over distances < 1 km) and evolution of traffic-generated UFPs for a real-world street network in central London was simulated by using the WRF-LES model (the large eddy simulation mode of the Weather Research and Forecasting modelling system) coupled with multicomponent microphysics. The neighbourhood scale dispersion of UFPs was significantly influenced by the spatial pattern of the real-world street emissions. Model output indicated the shrinkage of the peak diameter from the emitted profile to the downwind profile, due to an evaporation process during neighbourhood-scale dispersion. The dilution process and the aerosol microphysics interact with each other during the neighbourhood dispersion of UFPs, yielding model output that compares well with measurements made at a location downwind of an intense roadside source. The model captured the total SVOC concentrations well, with overestimations for gas concentrations and underestimations for particle concentrations, particularly of the lighter SVOCs. The contribution of the intense source, Marylebone Road (MR) in London, to concentrations at the downwind location (as estimated by a model scenario with emissions from MR only) is comparable with that of the rest of the street network (a scenario without emissions from MR), implying that both are important. An appreciable level of non-linearity is demonstrated for nucleation mode UFPs and medium range carbon SVOCs at the downwind receptor site. Graphical abstract: Image 1 Highlights: The spatial pattern of UFP dispersion at the neighbourhood scale was captured. Interaction of dilution and microphysical processes affected the UFP evolution. Smaller particles and medium carbon SVOCs had appreciable levels of non-linearity. Both Marylebone Road and the rest of the street network contributed to downwind UFP.